Cyberbullying and Legal Protection for Victims in the Digital Era: A Case Study on Social Media Platforms - Marjun; Saroji; Farhan, Farhan (Hakim: Jurnal Ilmu Hukum dan Sosial, 2025)
In the digital era, the widespread use of social media has led to a significant rise in cyberbullying cases, which have severe psychological, social, and legal consequences for victims. In Indonesia, the Electronic Information and Transactions Law (UU ITE) regulates cyberbullying; however, its implementation faces numerous challenges. This study aims to analyze the effectiveness of legal protection for cyberbullying victims in Indonesia and identify the challenges in enforcing existing regulations. Employing a juridical approach with qualitative analysis, this research examines relevant legal frameworks and conducts interviews with victims, legal practitioners, and law enforcement officials. Additionally, secondary data from official reports and court decisions are analyzed to understand the enforcement patterns of cyberbullying cases. Findings indicate that reported cyberbullying cases increased from 800 in 2018 to 3,800 in 2023, with the majority occurring on platforms such as TikTok and Instagram. However, only 20% of these reports were acted upon by authorities, and merely 5% resulted in legal consequences for perpetrators. Key obstacles in law enforcement include difficulties in identifying perpetrators using anonymous identities, lack of coordination between social media platforms and law enforcement agencies, and low public awareness regarding reporting mechanisms. This study contributes to policy recommendations aimed at strengthening legal protection for cyberbullying victims. These include regulatory reforms, increased digital literacy initiatives, and the optimization of technology in mitigating cyberbullying in Indonesia